Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Exiguobacterium enclense sp nov., isolated from sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Sonalkar, Vidya V.; Thorat, Meghana N.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Tang, Shan-Kun; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive bacterium, designated strain NIO-1109(T), was isolated from a marine sediment sample from Chorao Island, Goa, India. Phenotypic and chemotaxonomic characteristics and data from phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1109(T) was related to the genus Exiguobacterium. Strain NIO-1109(T) exhibited >98.0% 16S rRNA gene sequence similarity with respect to Exiguobacterium indicum HHS 31(T) (99.5%) and Exiguobacterium acetylicum NCIMB 9889(T) (99.1 %); the type strains of other species showed <98% similarity. Levels of DNA DNA relatedness between strain NIO-1109(T) and E. acetylicum DSM 20416(T) and E indicum LMG 23471(T) were less than 70% (33.0 +/- 2.0 and 37 +/- 32%, respectively). Strain NIO-1109(T) also differed from these two closely related species in a number of phenotypic traits. Based on phenotypic, chemotaxonomic and phylogenetic data, strain NIO-1109(T) is considered to represent a novel species of the genus Exiguobacterium, for which the name Exiguobacterium enclense sp. nov. is proposed. The type strain is NIO-1109(T) (=NCIM 5457(T)= DSM 25128(T)=CCTCC AB 2011124(T)).

Microbacterium enclense sp nov., isolated from sediment sample - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed Gulam (International Journal of Systematic and Evolutionary Microbiology, 2015)
A novel bacterium (strain NIO-1002(T)) belonging to the genus Microbacterium was isolated from a marine sediment sample in Chorao Island, Goa Province, India. Its morphology, physiology, biochemical features and 16S rRNA gene sequence were characterized. Cells of this strain were Gram-stain-positive, non-motile, non-spore-forming rods that formed yellow-pigmented colonies. It grew in 0-12 % (w/v) NaCl and at 25-37 degrees C, with optimal growth at 30 degrees C. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain NIO-1002(T) is associated with members of the genus Microbacterium, with highest sequence similarity with Microbacterium hominis CIP 105731(T) (98.1%) and Microbacterium testaceum KCTC 9103(T) (98.0 %). Within the phylogenetic tree, this novel strain shared a branching point with M. hominis CIP 105731(T). The DNA G+C content was 66.5 mol% and DNA DNA hybridization relatedness between NI-1002(T), M. hominis CIP 105731(T) and M. testaceum KCTC 9103(T) was 39.0 +/- 2.0 % and 41.0 +/- 2.0 %, respectively. The major fatty acids were ai-C-15:0, i-C-16:0 and al-C-17:0 and the diamino acid in the cell-wall peptidoglycan of NIO-1002(T) was lysine. Data obtained from DNA-DNA hybridization and chemotaxonomic phenotypic analysis support the conclusion that strain NIO-1002(T) represents a novel species within the genus Microbacterium. The name Microbacterium enclense sp. nov. is proposed, with NIO-1002(T) (=NCIM 5454(T)=DSM 25125(T)=CCTCC AB 2011120(T)) as the type strain.

Reclassification of bacillus isronensis shivaji et al. 2009 as solibacillus isronensis comb. nov and emended description of genus solibacillus krishnamurthi et al. 2009 - Mual, Poonam; Singh, Nitin Kumar; Verma, Ashish; Schumann, Peter; Krishnamurthi, Srinivasan; Dastager, Syed Gulam; Mayilraj, Shanmugam (International Journal of Systematic and Evolutionary Microbiology, 2016)
An investigation into the taxonomic position of Bacillus isronensis MTCC 7902(T) revealed that the strain shares a common phylogenetic lineage with Solibacillus silvestris MTCC 10789(T). It displays considerable overlap in phenotypic properties with the genus Solibacillus, including endospore shape and position, oxidase and catalase activities, presence of iso-C-15 : 0, C-16 : (1)omega 7c alcohol and iso-C-17 : 1 omega 7c as major cellular fatty acids, A4 alpha-type cell-wall peptidoglycan, polar lipids and menaquinone pattern. These features reinforce the findings of molecular phylogenetic analyses based on 16S rRNA gene, gyrB gene and 16S-23S internal transcribed spacer (ITS) region sequences and, in line with the recommendations of Kampfer et al. [Int J Syst Evol Microbiol 56 (2006), 781-786], provide justification for the transfer of Bacillus isronensis from the genus Bacillus to Solibacillus as Solibacillus isronensis comb. nov. The type strain is B3W22(T) (=MTCC 7902(T) =DSM 21046(T) =JCM 13838(T)). An emended description of the genus Solibacillus is also provided.

Microbacterium enclense sp. nov., isolated from sediment sample (vol 65, pg 2064, 2015) - Mawlankar, Rahul R.; Mual, Poonam; Sonalkar, Vidya V.; Thorat, Meghana N.; Verma, Ashish; Srinivasan, Krishnamurthi; Dastager, Syed G. (International Journal of Systematic and Evolutionary Microbiology, 2019)